2020
DOI: 10.1089/jop.2019.0148
|View full text |Cite
|
Sign up to set email alerts
|

Biodegradable Nanoparticles Based on Pseudo-Proteins Show Promise as Carriers for Ophthalmic Drug Delivery

Abstract: Purpose: Drug delivery to treat ocular diseases still is a challenge in ophthalmology. One way to achieve drug delivery that is investigated currently is topical administration of drug-loaded polymeric nanoparticles (NPs) that are able to penetrate ocular barriers. The purpose of this study was optimal preparation of NPs made from pseudo-proteins and evaluation of their ability to penetrate ocular tissues. Methods: Biodegradable NPs of various types were prepared by nanoprecipitation of pseudo-protein composed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 31 publications
0
2
0
Order By: Relevance
“…Corneal fluorescence was obtained as expected, while surprising results were the reaching of tissues such as the sclera and retina. Thus, they proved to be a promising delivery system for topical use in chronic eye diseases [ 139 ].…”
Section: Fluorescent Nanosystems In Ocular Applicationmentioning
confidence: 99%
See 1 more Smart Citation
“…Corneal fluorescence was obtained as expected, while surprising results were the reaching of tissues such as the sclera and retina. Thus, they proved to be a promising delivery system for topical use in chronic eye diseases [ 139 ].…”
Section: Fluorescent Nanosystems In Ocular Applicationmentioning
confidence: 99%
“…Moreover, rapid clearance remains a challenge for nanosystems as they need to release their payload before being eliminated from the eye. Many studies focus on assessing the distribution in various tissues once the formulation has been instilled into the eye [ 106 , 107 , 108 , 109 , 110 , 111 , 112 , 113 , 114 , 115 , 116 , 117 , 118 , 119 , 120 , 121 , 122 , 123 , 124 , 125 , 126 , 127 , 128 , 129 , 130 , 131 , 132 , 134 , 137 , 138 , 139 ]. Unfortunately, few studies focus on assessing how mechanisms including blinking, tear drainage and ocular metabolism may interact with nanosystems [ 66 , 115 ].…”
Section: Challenges and Future Perspectivesmentioning
confidence: 99%
“…Furthermore, in this work, we showed that the pseudo-protein 8L6 was the best in terms of particle size, stability, and cell compatibility. In another work [21], we prepared fuorescently tagged 8L6 pseudoprotein NPs and performed in vivo study of their penetration through ocular barriers using the experimental animals (wild-type C57BL/6 mice). Te in vivo study showed that the NPs are able to penetrate cornea and sclera and get even into the retina.…”
Section: Introductionmentioning
confidence: 99%